The Role of the Connection Book in Disciplining Students’ Five-Time Prayer In MI Integral Al-Ukhuwah - Rif'atul Ajizah; Sutrisno Sutrisno (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Prayer is the pillar of religion. Prayers must be accustomed to be carried out as early as possible. The education level of Madrasah Ibtidaiyah (MI) is the right school level to get children to pray five times a day. This study aims to determine the role of connection books in getting children to pray five times at home and school. This research is field research, which is descriptive and qualitative in nature. The methods used in collecting data are interviews, observation, and documentation. The subjects in this study were classroom teachers and parents of MI Integral Al-Ukhuwah students. While the object is the role of the connection book in disciplining students to pray five times a day at MI Integral Al-Ukhuwah. The results showed that the role of the connection book succeeded in getting students to pray five times both at home and at school. The conclusion of the connection book is a book that is used as a medium of communication between teachers and parents and is able to familiarize students with the five daily prayers.